Determinação do perfil molecular dos extratos de folhas de Carica papaya (L.) em busca de biomarcadores estágio-dependentes relacionados à doença da meleira do mamoeiro - Britto, Isabella Oliveira (2024)
Papaya Sticky Disease is caused by PMeV viral complex and poses a significant threat to papaya production worldwide. Infected plants remain asymptomatic until flowering and fructification, acting as silent reservoirs of the virus in the field. Secondary metabolites could act as potential biomarkers of disease progression and can be detected using chromatographic techniques for early disease diagnosis. In this study, molecular profiles of ethanolic extracts from C. papaya leaves in pre- and postflowering (2.5, 5.0, and 7.5 mg.mL-1) and fractions were evaluated by UV-Vis spectroscopy, reversed-phase chromatography, ion exchange chromatography, and mass spectrometry. The 7.5 mg.mL-1 concentration was selected as the experimental concentration for crude extracts. Chromatograms showed symmetrical peaks, eluted within similar retention time ranges across the three plant stages, with narrow base widths, similar peak shapes, and no tailing, suggesting the presence of a limited number of potentially isolable compounds. Analytical parameters indicated quantitatively larger chromatographic peaks in pre-flowering leaf extracts compared to post-flowering ones, reflecting a possible defense response against viral infection. Significant differences in chromatographic profiles between the different plant stages were observed, indicating the potential of these groups as biomarkers for Papaya Sticky Disease. This study developed a sensitive and reproducible chromatographic method to distinguish plant stages, identifying flavonoids and alkaloids as components of strategic groups related to the defense system against viral infections.